The importance of being called Lilia - Fallas Arias, Teresa (2015)
In this inquiry on the ‘autobiografía’ (autobiography) and the ‘curriculum operis’ of the Costa Rican writer Lilia Ramos I glimpse at the change of name scrounged by Lilia since her infancy, as a kind of incantation in which she asserts and reinvents herself since she was a little girl, to shine intellectually, academically and professionally as an adult, when she manages to transmute her ‘ugliness’ complex into vital resistance. I focus this reading on the perspective written by Judith Butler in the book Language, power and identity, a text in which the rhetoric refers to the violent and injurious action of names and their relationship with personal identity.